KAJIAN KENYAMANAN PADA RUANG TERBUKA HIJAU BERDASARKAN THI DI DESA SAWAHAN, KECAMATAN NGEMPLAK, KABUPATEN BOYOLALI - Adhistie Fadila Setyaputri; Danila Desti Ramadhani; Wahyu Kisworo (Nusantara Hasana Journal, 2023)
The large number of vehicles passing by on the toll road, as well as the presence of factory fumes and land conversion in Sawahan Village have caused an increase in climate change. Climate change that tends to occur from this is an increase in air temperature and a decrease in humidity. An increase in air temperature and a decrease in humidity in an area can cause a decrease in comfort in that area. If comfort is reduced, it will have a negative impact on humans, animals and plants. Humans will feel uncomfortable and will interfere with their productivity as well as animals, while plants will wither and die over time. This study aims to determine the biodiversity found in several green open spaces in Sawahan Village and determine the comfort level in Sawahan Village based on an assessment obtained from the Temperature Humidity Index (THI). This research was conducted using descriptive quantitative analysis method. From this research, it resulted that flora biodiversity has a strong correlation with comfort, even though all locations include green open spaces, the differences in flora biodiversity will affect the level of comfort. shady and cool compared to locations with lots of grass. Even though they are both green, the level of coolness that is felt is much different.